2017
DOI: 10.1002/cne.24235
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the septohippocampal cholinergic fiber system in experimental epilepsy

Abstract: The septohippocampal cholinergic neurotransmission has long been implicated in seizures, but little is known about the structural features of this projection system in epileptic brain. We evaluated the effects of experimental epilepsy on the areal density of cholinergic terminals (fiber varicosities) in the dentate gyrus. For this purpose, we used two distinct post-status epilepticus rat models, in which epilepsy was induced with injections of either kainic acid or pilocarpine. To visualize the cholinergic fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 93 publications
(133 reference statements)
6
13
0
Order By: Relevance
“…Two-way ANOVA of these data revealed a significant effect of KA injection (F(1,23)=30.12; p<0.001), a significant effect of SAP pretreatment (F(1,23)=82.47; p<0.001), and a significant interaction between the two effects (F(1,23)=20.82; p<0.001). Consistent with our previous report (Soares et al, 2017), KA-treated rats had almost as twice as many VAChT-stained neurons in the MS/DB comparing to controls (p<0.001 for post-hoc test). Interestingly, SAP-pretreated rats had somewhat (25%) lower number of VAChT-IR neurons when compared to control (p<0.05) and SAP-pretreatment prevented the KA-induced increase in the number of VAChT-IR septal cells (p<0.001 for comparison between the KA group and SAP+KA group).…”
Section: Total Number and Somatic Volume Of Vacht-immunoreactive Cellssupporting
confidence: 92%
See 2 more Smart Citations
“…Two-way ANOVA of these data revealed a significant effect of KA injection (F(1,23)=30.12; p<0.001), a significant effect of SAP pretreatment (F(1,23)=82.47; p<0.001), and a significant interaction between the two effects (F(1,23)=20.82; p<0.001). Consistent with our previous report (Soares et al, 2017), KA-treated rats had almost as twice as many VAChT-stained neurons in the MS/DB comparing to controls (p<0.001 for post-hoc test). Interestingly, SAP-pretreated rats had somewhat (25%) lower number of VAChT-IR neurons when compared to control (p<0.05) and SAP-pretreatment prevented the KA-induced increase in the number of VAChT-IR septal cells (p<0.001 for comparison between the KA group and SAP+KA group).…”
Section: Total Number and Somatic Volume Of Vacht-immunoreactive Cellssupporting
confidence: 92%
“…Despite the existing evidence for the involvement of cholinergic transmission in seizures and epilepsy, the functional implications of the cholinergic fiber network reorganization in epileptic brain are not clear. It has been suggested that such a reorganization, namely sprouting of the cholinergic fibers into molecular layer of the dentate gyrus and their removal from the dentate hilus, would make hippocampal circuits hyperexcitable (Soares et al, 2017), a mechanism which has long been implicated in neuropathology of TLE (Tauck and Nadler, 1985;Zeng et al, 2009). This possibility is supported by the findings showing that application of acetylcholine to hippocampal slices from epileptic rats, but not from control rats, produces epileptic-like neuronal discharges (Zimmerman et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The degree of damage to such structures, notably the nucleus basalis, correlates with the degree of smell dysfunction observed among a range of neurodegenerative diseases [10]. Moreover, damage to such forebrain cholinergic centers has been linked to hippocampal epileptogenesis [45]. As reviewed in the latter paper, several studies have found that immunotoxic lesions of septal cholinergic cells in rats increase seizure susceptibility and exacerbate seizure-induced neuronal loss in the hilus of the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that right following KA-induced epilepsy, hippocampal neurons strongly expressed immediate early genes c-Fos and c-Jun, which encode transcription factors (Kim et al, 2008 ). In the brain of KA model, a bunch of neurotransmitters, receptors and ion channels were observed increased including voltage-gated sodium channel Nav1.6 (Zhu et al, 2016 ), Na + /K + /Cl − cotransporter (Nogueira et al, 2015 ), metabotropic glutamate receptors (mGluRs) especially mGluR2/3 (Caulder et al, 2014 ) and mGluR5 (Medina-Ceja and García-Barba, 2017 ), ATP-activated P2Y receptors (Alves et al, 2017 ) and acetylcholine neurotransmission (Soares et al, 2017 ). Besides the activation of these excitatory mechanisms, other mechanisms involved in KA-induced hyperexcitability have also been documented.…”
Section: Discussionmentioning
confidence: 99%